Vapor pressure deficit predicts epiphyte abundance across an elevational gradient in a tropical montane region. Issue 12 (1st December 2017) - Gotsch, Sybil G.; Davidson, Kenneth; Murray, Jessica G.; Duarte, Vanessa J.; Draguljić, Danel
Abstract : PREMISE OF THE STUDY: Tropical Montane Cloud Forests (TMCFs) are important ecosystems to study and preserve because of their high biodiversity and critical roles in local and regional ecosystem processes. TMCFs may be particularly affected by changes in climate because of the narrow bands of microclimate they occupy and the vulnerability of TMCF species to projected increases in cloud base heights and drought. A comprehensive understanding of the structure and function of TMCFs is lacking and difficult to attain because of variation in topography within and across TMCF sites. This causes large differences in microclimate and forest structure at both large and small scales. METHODS: In this study, we estimated the abundance of the entire epiphyte community in the canopy (bryophytes, herbaceous vascular plants, woody epiphytes, and canopy dead organic matter) in six sites. In each of the sites we installed a complete canopy weather station to link epiphyte abundance to a number of microclimatic parameters. KEY RESULTS: We found significant differences in epiphyte abundance across the sites; epiphyte abundance increased with elevation and leaf wetness, but decreased as vapor pressure deficit (VPD) increased. Epiphyte abundance had the strongest relationship with VPD; there were differences in VPD that could not be explained by elevation alone. CONCLUSIONS: By measuring this proxy of canopy VPD, TMCF researchers will better understand differences in microclimate and plant community composition across TMCF sites. Incorporating such information in comparative studies will allow for more meaningful comparisons across TMCFs and will further conservation and management efforts in this ecosystem.